Sémantographie du domaine "travail" dans la haute-ville et dans la basse-ville de Québec - Maranda, Pierre (Anthropologica, 2022)
Semantography is a subfield of semiography, which is a method of description of semiotic data. It is applied in this paper to the domain "Work" in a sample of Upper and Lower Town Quebec City residents. The results show that "Work" is more closely related to "Family" in the Lower Town than in the Upper Town. Semantic inertia and momentum appear to be defineable within a structure of appropriation related to socio-economic factors.